Pengaruh Terapi Massage Effleurage terhadap Penurunan Nyeri Haid Pada Remaja Putri di Klaten - Devi Permata Sari; Sri Sat Titi Hamranani (MOTORIK Jurnal Ilmu Kesehatan, 2019)
Menstrual pain is a frequent problem experienced by adolescent girls. Menstrual pain arising from the contractions of the distritmia the myometrium. Teenagers who experience menstrual pain will have an impact anxiety can affect the occurrence of the decrease in the activities of the school and the achievement, therefero, to reduce the pain of mentruation is by way of a therapeutic massage effleurage. Research purpose Determine the effect of therapeutic massage effleurage to decrease the pain of menstruation in adolescent girls in SMA Muhammadiyah 1 Klaten. Desain observational Using quasy experiment design with non-equivalent control grup and using the test mann whitney test. Sampling technique using purposive sampling techique as many as 34 respondents. The measurement of pain level using the NRS (Numerical Rating Scale). The results showed that the pain scale of the respondent in the experimental group after done message effleurage pain scale minimum 1 maximum value of 4, with avarage pain scale 2.24 ± 0.970, while the second measurement scale of pain for a minimum of 2, maximum score is 5, with average pain scale 3.71 ± 1.047. the results of data analysis using test mann whitney test obtained Pv = 0.00 < α = 0.05. Conclussion is therapy massage effleurage infuential to reduce pain menstruation.